Long‐term survival of patients with relapsed/refractory acute lymphoblastic leukemia treated with blinatumomab. Issue 4 (3rd November 2020) - Topp, Max S.; Gökbuget, Nicola; Zugmaier, Gerhard; Stein, Anthony S.; Dombret, Hervé; Chen, Yuqi; Ribera, Josep‐Maria; Bargou, Ralf C.; Horst, Heinz‐August; Kantarjian, Hagop M.
Abstract : Background: Blinatumomab is a CD19 BiTE (bispecific T‐cell engager) immuno‐oncology therapy that mediates the lysis of cells expressing CD19. Methods: A pooled analysis of long‐term follow‐up data from 2 phase 2 studies that evaluated blinatumomab in heavily pretreated adults with Philadelphia chromosome–negative, relapsed/refractory B‐cell precursor acute lymphoblastic leukemia was conducted. Results: A total of 259 patients were included in the analysis. The median overall survival (OS) among all patients, regardless of response, was 7.5 months (95% confidence interval [CI], 5.5‐8.5 months); the median follow‐up time for OS was 36.0 months (range, 0.3‐60.8 months). The median relapse‐free survival (RFS) among patients who achieved a complete remission (CR) or complete remission with partial hematologic recovery (CRh) in the first 2 cycles (n = 123) was 7.7 months (95% CI, 6.2‐10.0 months); the median follow‐up time for RFS was 35.0 months (range, 9.5‐59.5 months). OS and RFS plateaued with 3‐year rates of 17.7% and 23.4%, respectively. The cumulative incidence function of the time to relapse, with death not due to relapse considered a competing risk, for patients who achieved a CR/CRh within 2 cycles of treatment also plateaued with a 3‐year relapse rate of 59.3%. For patients who achieved a CR/CRh with blinatumomab followed by allogeneic hematopoietic stem cell transplantation while in continuous CR, the median OS was 18.1 months (95% CI, 10.3‐30.0 months) with a 3‐year survival rate of 37.2%. Conclusions: These data suggest that long‐term survival is possible after blinatumomab therapy. Lay Summary: Immuno‐oncology therapies such as blinatumomab activate the patient's own immune system to kill cancer cells. This study combined follow‐up data from 2 blinatumomab‐related clinical trials to evaluate long‐term survival in patients with relapsed and/or refractory B‐cell precursor acute lymphoblastic leukemia at high risk for unfavorable outcomes. Among patients who achieved a deep response with blinatumomab, one‐third lived 3 years or longer. These findings suggest that long‐term survival is possible after treatment with blinatumomab. Abstract : Patients achieving remission after blinatumomab can have a durable response. The survival plateau indicates a high probability of a cure in those patients responding to blinatumomab and alive after 3 years.